Wybrane kierunki zmian w obszarze strategicznego zarządzania organizacją - Stańczyk-Hugiet, Ewa (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The paper concerns some changes in nature of management system. Strategic management is especially the main interest. Here are indicated four trends in entire strategic management: from economic profit to economic rent, from organizational routines to dynamic capabilities, from strategic fit to organizational fitness, from strategic planning to strategy implementation. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 192-197